Peningkatan Pengetahuan Masyarakat Terhadap Penyakit Diabetes Melitus Melalui Sosialisasi dan Pemeriksaan di Desa Tanjung Garbus II Kecamatan Pagar Merbau - Hutagalung, Suzanne Carmentine (Yayasan Daarul Huda Kruengmane, 2025)
This community service program aims to improve the knowledge and skills of families, primarily targeting the elderly. The implementation method consists of preparation, implementation, and evaluation. Activities include outreach and examinations on diabetes mellitus, as well as self-monitoring of blood sugar levels. Diabetes mellitus is a chronic disease that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Uncontrolled high blood glucose levels can cause serious damage to the heart, blood vessels, eyes, kidneys, and nerves. Counseling is the primary prevention of diabetes mellitus. The incidence of diabetes increases annually, not only in adults but also in children, which can impact the nation's future productivity. The partner's problem is that diabetes cases are now occurring not only in adults and the elderly but also in children and adolescents. The solution offered is to provide outreach and training on diabetes prevention and early detection in the elderly.